Diagnóstico para mejorar la eficiencia energética en la escuela Politécnica del Ejército extensión Latacunga 2013.Elaboración de un sistema de gestión energética según la norma internacional ISO 50001. - Torres Vásquez, Katya Mercedes (2013)
This research presents the energy audit results conducted at Escuela Politécnica del Ejército, Latacunga Extension, whose goal was to determine if there is a use, consumption and energy performance suitable. Between the energy used, electricity is the most consumed. It follows a methodology with Total Energy Management tools used in order to collect and analyze results. For that, through the analysis was determined consume indicators establish the relation of energetic performance and the energy used for students teachers and administrative personnel. The Electricity Quality study technical data useful for the propose of improvement plans related to the harmonic distortion produced by nonlinear loads connected to supply netwok. A major requirement is to determine the baseline power. The most significant occurrences in the electrical energy losses are determined. It also seeks to raise awareness among university members on the proper use of energy resources. Based on the recommendations on the ISO 50001 norm make standard plan Energy Management System to promote the mitigation of global energy problem.